Youth as Architects of Social Change : Global Efforts to Advance Youth-Driven Innovation - Bastien, Sheri; Holmarsdottir, Halla B. (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This edited collection outlines the issues central to youth engagement in research and social innovation. Youth-driven innovation for social change is increasingly recognized as holding potential for the development of sustainable strategies to tackle some of the most pressing global challenges of our time. The contributors provide additional knowledge concerning what actually constitutes an enabling environment, as well as the most effective approaches for engaging youth as architects of change. While sensitive to the need for contextual appropriateness, the volume contributes to the development of shared understandings and frameworks for engaging and spurring youth-driven innovation for social change worldwide. Youth-Driven Social Innovation showcases examples of youth engagement in frugal and reverse innovation worldwide, alongside examples which demonstrate the tremendous potential of South-South learning, but also learning and youth innovation in the Global North. It will be of interest to students and scholars across a range of disciplines including education, sociology, anthropology, public health, and politics.